Molecular characterization of a novel Aureusvirus infecting elderberry (Sambucus nigra L.) - Šafářová, Dana; Vavroušková, Karolína; Candresse, Thierry; Navrátil, Milan (PloS one, 2018)
A novel virus infecting elderberry was identified by high-throughput Illumina sequencing of double strand RNAs isolated form elderberry leaves. The complete genome sequence obtained (4512 nucleotides in length) shows an organization typical for aureusviruses, with five open reading frames (ORFs) and the typical ORF1-RT expression by the readthrough of an amber stop codon. The analysis of the RNA-dependent RNA polymerase (RdRp) and coat protein (CP) sequences showed the highest identity (respectively 75.7% and 55%) with the corresponding amino acid sequences of Pothos latent virus. These two values, below the species demarcation criteria for the genus, indicate that the detected virus is a new member of genus Aureusvirus, family Tombusviridae, with the proposed name Elderberry aureusvirus 1 (ElAV1). A survey confirmed the wide distribution of ElAV1 in elderberry in the Czech Republic. Phylogenetic analyses of RdRp and CP sequences showed distinct microevolution of geographically separated isolates, with a tendency for isolates coming from close localities or from the same region to cluster together but heterogeneity of viral populations down to a local scale was also observed. The symptomatology of the new virus is not fully clear, but many infected trees were either asymptomatic or showed mild chlorotic mosaics. More severe symptoms, potentially impacting yields of flowers or berries, were observed in plants with mixed infections of ElAV1 and other elderberry viruses. Further efforts are now needed to determine ElAV1 prevalence outside the Czech Republic and to unravel its epidemiology.
Keywords: Sambucus nigra; genom virový; bez černý; Genome, Viral; Phylogeny; Tombusviridae; fylogeneze; nemoci rostlin; Plant Diseases